THE THE ROLE OF THE CONGRESS OF LOCAL AND REGIONAL AUTHORITIES OF THE COUNCIL OF EUROPE - Tomašević, Mateja (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
The need for lower territorial forms of government appeared in the early fifties of the last century when the Conference of Local Authorities was founded. However, in the seventies, with the emergence of increasing regionalization, there was a need and advocacy for greater democracy of local and regional dimensions. Great recognition of local and regional democracy came in 1985 when the European Charter of Local Self-Government was adopted, while in the early nineties, the Congress of Local and Regional Authorities of the Council of Europe was established, which replaced the previous Conference of Local Authorities. Since then, the democratic aspect of dividing power into local and regional has been advocated increasingly in Europe. Congress has established several instruments to preserve and promote democracy at lower levels of government. To consolidate territorial democracy, and to ensure the uniform application of local and regional democracies, the Congress strengthened cooperation with member states and established three committees that evaluate national legal frameworks, exchange good practices, and guide local and regional democracies of signatory states. At the same time, the Congress ensures the protection and respect of fundamental political and civil rights and freedoms. All the mentioned factors and instruments show that regional democracy is impossible without regional autonomy, and the European Charter of Local Self-Government serves as a source of inspiration for countries that decide to establish or reform their local and regional authorities, as well as a guideline and guiding thought for signatories who already act according to it.